The Role of Customary Law in the National Legal Structure of the Archipelago - Amalia Tasya (PT. Anagata Sembagi Education, 2025)
Customary law plays an important role in the national legal structure in the archipelago, which is known for its diversity of tribes, cultures, and traditions. This article examines how customary law functions and interacts with the positive legal system in Indonesia and its contribution to the formation and implementation of national law. The main focus of this study is the analysis of the recognition, protection, and integration of customary law within the state legal framework, as well as the challenges and opportunities that arise in the harmonization process. Using a case study approach and comparative analysis, this article explores various models of interaction between customary law and positive law in various regions in the archipelago. This study also discusses the role of customary institutions in enforcing customary law and the contribution of customary law to preserving local cultural identity. The results of the study show that although the integration of customary law with national law faces various challenges, customary law still makes a significant contribution to maintaining social justice and protecting the rights of indigenous peoples. This article aims to provide insight into the importance of recognizing and respecting customary law in the national legal system and to encourage discussion on how the integration of customary law can improve the quality and justice of law in the archipelago